Inactivation of cofilin-1 in Mcpt5-Cre-nf-Cfl1fl/fl mice prevents the formation of connective tissue mast cells without affecting basophils: a new tool to investigate the specific role of CTMCs in disease - Kramer, Johanna; Schneider, Jakob; Liu, Huiying; Silva-Vilches, Cinthia; Moos, Sonja; Kamenjarin, Nadine; Hodapp, Katrin; Tsvilovskyy, Volodymyr; Freichel, Marc; Probst, Hans Christian; Mahnke, Karsten; Kurschus, Florian C.; et al. (Frontiers in Immunology, 2026)
Actin-binding proteins play a critical role in regulating the dynamic rearrangement of the actin cytoskeleton, which is essential for maintaining cellular homeostasis and facilitating various processes in eukaryotic cells. Cofilin-1 (Cfl1), an actin-binding protein, promotes the severing and depolymerization of actin filaments. To investigate the function of Cfl1 in mast cells, we generated Mcpt5-Cre-nf-Cfl1fl/fl knock-in mice, expressing a non-functional form of Cfl1 (nf-Cfl1) instead of wildtype Cfl1 under the control of the connective tissue mast cell (CTMC)-specific promoter mast cell protease 5 (Mcpt5). Expression of nf-Cfl1 resulted in the complete absence of CTMCs. Notably, normal numbers of basophils were observed, in contrast to other mast cell-deficient mice. Interestingly, an inducible knock-in of nf-Cfl1 in mature mast cells did not affect the survival of mature mast cells. The Mcpt5-Cre-nf-Cfl1fl/fl mice lacking CTMCs showed impaired induction of systemic anaphylaxis. However, they remained fully susceptible to 1-fluoro-2,4-dinitrobenzene-induced contact hypersensitivity and imiquimod-induced psoriasis-like dermatitis. In addition, clearance of vaccinia virus skin infection was unaltered. Thus, this study demonstrates that CTMCs are not essential in these inflammatory skin diseases. Deviating results in some other mast cell-deficient models suggest that the concomitant lack of basophils or residual CTMCs in these mouse models influence disease outcome. Taken together, the complete absence of CTMCs and the preserved presence of basophils in Mcpt5-Cre-nf-Cfl1fl/fl mice establishes this model as a valuable tool for studying the specific role of CTMCs in different diseases.